2020
DOI: 10.1037/per0000371
|View full text |Cite
|
Sign up to set email alerts
|

Response perseveration and the triarchic model of psychopathy in an undergraduate sample.

Abstract: This study aimed to extend previously reported links between distinctive configurations of traits in the psychopathic personality and maladaptive response perseveration, by examining performance in the Card Perseveration Task (CPT) within the framework of the triarchic model of psychopathy in a mixed-gender undergraduate sample. A computerized version of the CPT was administered to 222 undergraduates (142 women) assessed for triarchic psychopathy dimensions using the Triarchic Psychopathy Measure (TriPM). Mala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 58 publications
0
4
3
Order By: Relevance
“…2). This finding is somewhat inconsistent with previous research that found individuals with high Boldness scores demonstrate behavioral and psychophysiological insensitivity to punishment cues (Ribes-Guardiola et al, 2020; Vaidyanathan et al, 2009). The findings reported in the current study do parallel reports from one recent study (Ribes-Guardiola et al, 2020), which found that females with high Boldness scores demonstrated behavioral insensitivity to punishment feedback, whereas in males, Boldness scores were not associated with a change in behavioral response.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…2). This finding is somewhat inconsistent with previous research that found individuals with high Boldness scores demonstrate behavioral and psychophysiological insensitivity to punishment cues (Ribes-Guardiola et al, 2020; Vaidyanathan et al, 2009). The findings reported in the current study do parallel reports from one recent study (Ribes-Guardiola et al, 2020), which found that females with high Boldness scores demonstrated behavioral insensitivity to punishment feedback, whereas in males, Boldness scores were not associated with a change in behavioral response.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is somewhat inconsistent with previous research that found individuals with high Boldness scores demonstrate behavioral and psychophysiological insensitivity to punishment cues (Ribes-Guardiola et al, 2020; Vaidyanathan et al, 2009). The findings reported in the current study do parallel reports from one recent study (Ribes-Guardiola et al, 2020), which found that females with high Boldness scores demonstrated behavioral insensitivity to punishment feedback, whereas in males, Boldness scores were not associated with a change in behavioral response. Note that Boldness scores were not associated with neural response to feedback regarding loss, which suggests that although there is increased left NAcc activation in anticipation of loss in males with high Boldness scores, their response when receiving feedback of loss compared with no loss is unrelated.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Boldness is the only triarchic disposition consistently related to low neuroticism and high extraversion (e.g., Miller et al, 2016; Poy et al, 2014), personality traits theoretically associated with a weak behavioral inhibition system (Gray, 1987; Gray & McNaughton, 2000), responsible for inhibiting or regulating approach behavior that might lead to adverse outcomes in response to threats of punishment. Indeed, research is beginning to learn about the specific role of boldness in some well-documented threat processing psychopathic deficits including maladaptive response perseveration in the face of punishment (Ribes-Guardiola et al, 2020), diminished startle responses to threat pictures (Este-ller et al, 2016), and reduced amplitudes of late positive potentials to aversive signals (Ellis et al, 2017; Paiva et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, boldness has shown consistent negative associations with self-report measures of fearfulness/anxiety and internalizing symptomatology (Latzman et al, 2020; Poy et al, 2014). It is worth nothing that boldness has been related to mal-adaptive response perseveration in the face of increasing punishment contingencies (Ribes-Guardiola et al, 2020) but also to an enhanced task switching performance under threat conditions (Yancey et al, 2019), suggesting that resistance to the impact of danger or punishment cues might involve adverse outcomes or an adaptive resilient style depending on the situation. Boldness has recently been shown to predict greater emotional well-being during COVID-19 outbreak (Sica et al, 2021) and reduced frequency of protective behaviors (Paiva et al, 2021), supporting the idea that boldness’ protection from emotional distress may in turn lead to behaviors that increase the risk of getting the disease.…”
mentioning
confidence: 99%